A Remarkable Case of Acute Motor-Sensory Axonal Polyneuropathy (AMSAN) Variant of Guillain Barré Syndrome, in a Diabetic Patient Infected With COVID-19: A Case Report and Review of the Literature - Ali, Sajjad; Karam, Alvina; Lalani, Aarish; Jawed, Sadia; Moin, Musfirah; Douba, Zain; Ali, Murtaza (Frontiers in Neurology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease- 2019 (COVID-19), has been a global epidemic in our healthcare system. SARS-CoV-2 primarily affects the respiratory system, but neurological involvement has also been reported, including Guillain–Barré syndrome (GBS) development. A 58-year-old male with known co-morbid hypertension and type 2 diabetes mellitus presented to the emergency room with complaints of worsening shortness of breath, dry cough, and fever for the past ten days. On day 20 of hospitalization, he developed neurological symptoms after being tested positive for COVID-19. A neuron electrophysiology study was conducted to evaluate neurological symptoms and suggested that the patient suffers from acute motor-sensory axonal polyneuropathy (AMSAN). CSF analysis showed elevated protein levels that confirmed the diagnosis of GBS. He was subsequently treated with oral prednisolone and IVIG, which improved neurological symptoms. Ever since the emergence of COVID-19, GBS has surfaced as to its potentially dangerous outcome. Healthcare professionals should be mindful of GBS and should rule it out in anyone having sensory symptoms or weakness during or after a COVID-19 infection. Its early detection and treatment can result in improved clinical outcomes.